PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA MENGGUNAKAN ALAT PERAGA KARTU BILANGAN PADA MATERI STATISTIKA KELAS VIII MTS DESA SAWAH - Yostra Reza; Zulhendri; Astuti; Adityawarman Hidayat; Zulfah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Realistic Mathematics Education (RME) approach assisted by number card teaching aids on students' understanding of mathematical concepts in the statistics material for eighth-grade students at MTs Desa Sawah. The background of this study is based on the low level of students' concept comprehension due to teacher-centered learning and insufficient involvement of students in real activities. The Realistic Mathematics Education (RME) approach was chosen because it emphasizes contextual learning experiences and the construction of meaning through mathematical activities relevant to everyday life. This study uses a quantitative method with a quasi-experimental design of the nonequivalent control group type. The research subjects were two eighth-grade classes consisting of an experimental class and a control class. Data collection techniques were carried out through tests (pretests and posttests), observation, and documentation. The test instruments were first tested for validity and reliability. The data analysis techniques included tests for normality, homogeneity, t-tests, and N-Gain using SPSS 29 software. The results of the study showed that there was a significant difference between the average posttest scores of the experimental class and the control class. This is evidenced by the t-test results showing a significance value (2-tailed) < 0.05, which is 0.017. Thus, it can be concluded that the Realistic Mathematics Education (RME) approach assisted by number card teaching aids has a positive effect on improving students' mathematical concept understanding. This approach can serve as an effective alternative learning method to enhance students' understanding, particularly in statistics material.